THE EFFECTIVENESS OF SOURSOP (Annona muricata L.) BOOKING WATER ON BLOOD BIOCHEMICAL LEVELS OF MOUSE (Mus musculus) INDUCED RHODAMIN B - Pramita Wally (International Journal of Multidisciplinary Research and Literature, 2022)
This study aimed to determine the effect of giving soursop (Annona muricata L.) boiled water for 14 days on biochemical blood levels, including SGOT, SGPT, urea, and creatinine in the balb-C strain mice induced by rhodamine B orally. Twenty-five male mice were divided into five groups, namely groups I and II as negative control and positive control. Group III was treated with soursop leaf boiled water at 3.64 mg/mouse, and group IV was treated with soursop leaf boiled water at 7.28 mg/mice. Mice, while group V was treated with 10.92 mg/mouse of soursop leaf boiled water. The treatment was carried out for 14 days by giving soursop leaf boiled water seven days after administration of rhodamine B. On days 1, 7, and 14, the mice took intracardially, and then the levels of SGPT, SGOT, urea, and creatinine were measured. The data were then analyzed using the One way ANOVA test and continued with the LSD test. One-way ANOVA test results showed that giving soursop leaf boiled water had a significant effect on reducing SGOT, SGPT, urea, and creatinine (p<0.05). The results of the LSD test showed significant differences between levels of SGOT SGPT, urea, and creatinine in the group before treatment, after administration of rhodamine B, and after administration of soursop leaf boiled water. It concludes that the treatment of soursop (Annona muricata L.) cooked in the water had the most practical effect in neutralizing the damage to liver and kidney cells of mice exposed to rhodamine B. Because it contains antioxidants, the water that boiled with soursop leaf provided a cytoprotective effect by neutralizing the free radicals caused by rhodamine B